Association between Levels of IgA Antibodies to Tissue Transglutaminase and Gliadin-Related Nonapeptides in Dermatitis Herpetiformis - Justyna Gornowicz-Porowska; Monika Bowszyc-Dmochowska; Agnieszka Seraszek-Jaros; Elżbieta Kaczmarek; Marian Dmochowski (The Scientific World Journal)
Dermatitis herpetiformis (DH) is an autoimmunity-driven inflammatory blistering dermatosis associated with a gluten-dependent enteropathy. Tissue transglutaminase (tTG) and nonapeptides of gliadin (npG) are considered in its pathomechanism/diagnostics. Here, the diagnostic accuracy of anti-tTG/anti-npG IgA ELISAs in Slavic DH patients with active skin rash was assessed through creating receiver operating characteristic (ROC) curves, determining cutoff values, and calculating correlations between levels of anti-tTG/anti-npG IgA in DH, IgA/neutrophil-mediated non-DH patients and healthy persons. Altogether, sera from 80 Slavic individuals were examined. There were negligible differences between cutoff points obtained by the ELISAs manufacturer and those in this study. There were statistically significant correlations between levels of anti-tTG/anti-npG IgA in both DH group and the group of IgA/neutrophil-mediated non-DH dermatoses. There was no such correlation in healthy controls. It seems that IgA autoantibodies to tTG and npG in the IgA/neutrophil-mediated DH are produced in the coordinated way implying their causal relationship.